2013
DOI: 10.5539/jfr.v3n1p61
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation Quality and Efficiency of Lactobacillus casei by Spray Drying Using Maltodextrin and Vegetable Extracts

Abstract: Survival and quality efficiency of Lactobacillus casei microencapsulated by spray drying using different vegetable extracts (asparagus, artichoke, orange or grapefruit peel) were evaluated. Aqueous suspensions of the vegetable extracts with or without maltodextrin (adjusting to 25% w/w) were prepared for the microencapsulation of L. casei. The evaluated spray drying conditions were at a fixed air inlet temperature (Tin) of 145 °C and varying the aqueous suspensions flux (Q) of 10 or 15 g/min. Survival of L. ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Spray dried microcapsules commonly have a particle diameter range of 5 to 100 µm (Fritzen-Freire et al, 2012;Hernández-Carranza et al, 2013;Rokka & Rantamaki, 2010). It has been reported that small particle sizes facilitates a greater contact surface for the nutrients availability (Avila-Reyes et al, 2014).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Spray dried microcapsules commonly have a particle diameter range of 5 to 100 µm (Fritzen-Freire et al, 2012;Hernández-Carranza et al, 2013;Rokka & Rantamaki, 2010). It has been reported that small particle sizes facilitates a greater contact surface for the nutrients availability (Avila-Reyes et al, 2014).…”
Section: Physical Propertiesmentioning
confidence: 99%
“…Standard deviation was applied for determination of significant difference between means of moisture content, colour readings, cell counts and antioxidant activities 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Spray dried microcapsules commonly have a particle diameter range of 5 to 100 µm (FritzenFreire et al, 2012;Hernández-Carranza et al, 2013;Rokka & Rantamaki, 2010). It has been reported that small particle sizes facilitates a greater contact surface for the nutrients availability (Avila-Reyes et al, 2014).…”
Section: Physical Propertiesmentioning
confidence: 99%